Compressive myelopathy presenting with paraparesis in pediatric age - Dr. V. A. Kotrashetti; Dr. Vijay Baburao Sonawane; Dr. Shweta Ravindran Nair; Dr. Kapil Bainade; Dr. Amit Vatkar; Dr. Samarth Gupta (Pediatric Review: International Journal of Pediatric Research, 2020)
Compressive myelopathy is a common presentation of the adult age group secondary to degenerating etiologies. Trauma is a rare cause of compressive myelopathy, especially in the pediatric age group as the pediatric spine is more elastic than that of adults, especially below 8 years of age. Boys are more commonly injured as compared to girls. The present study reports a case of a six-year-old female patient of compressive myelopathy presenting with jerks with progressive paraparesis. MRI shows posterior subluxation of dens (C2) attached to C2 vertebral effacing anterior – subarachnoid space and indenting spinal cord.